Pengamatan Kebijakan Pendidikan pada Madrasah di Indonesia - Muhammad Iqbal; M. Hangga Reksa B. R. Sirait; Dara Mayang Sari; Echa Putri Khairani; Mai Syaroh Harahap (Departement of Mathematics Education, 2023)
This study aims to determine the role of madrasas in the national education system, madrasa problems, opportunities and challenges of madrasas. The method used in this study is a literature study by collecting secondary data from various references in the form of books and journals, then conducting a descriptive analysis of the data which is presented in detail. In essence, madrasas have a qualified position in nation building, but unfortunately currently education in madrasas is considered